Puerto Rican Youth in Drug Treatment Facilities: Who Volunteers for HIV Testing? - Vélez, Carmen Noemi; Rodríguez, Luis A.; Schoenbaum, Ellie; Ungemack, Jane A. (Puerto Rico Health Sciences Journal, 2025)
see manuscript